Identidade televisual: autopromocionalidade e autorreferencialidade - Menezes, Darciele Paula Marques (2012)
This dissertation proposes to examine the actions of self-promoting and self-referential character undertaken by the television companies inside their own schedule, in order to constitute yours identity and to promote yours image and trademark: in this somewhat circular gear, usually use its communication and discursive device for their own benefit. Thus, the research analyzes, in terms of a discursive semiotics, some of the procedures adopted by the television companies to constitute its identity, to project its image and trademark and to promote the quality of its products, in order to make public viewer loyal. This is a difficult task, especially in the case of affiliated stations that need to develop this promotional process in two directions, not always convergent: the head and its own network. To realize the objectives, the research has as its object of study two sitcoms, The New Program (RGT, 2004) and Off the Air (RBS TV, 2011), whose central theme is exactly the televisual production and television companies backstages.